The Mother’s Role in Giving Healthy Eating Patterns for Children Age 3-5 Years - Kristianingrum, Dhita Yuniar; Aini, Inayatul; Shofiyah, Siti; Setiarini, Dwi Anik Karya; Novitasari, Rista (Jurnal MIDPRO, 2023)
A eating patterns  is the way in which a person to choose, and using a food ingredient in food consumption every day which include the type of food, number of food and eating frequency. Based on the preliminary study on August 15, 2019 in Brambang Village, Jombang District. On 30 mothers who have children aged 3-5 years, 76,6%  mothers do not know how to gives a healthy eating patterns and 24,4% others know how to gives a healthy eating patterns for children. The purpose of this research is to know the role of the mother within gives a healthy eating patterns for children age 3-5 years in Brambang Village, Jombang District.The design of this research is a descriptive research, with the population of mothers who has a toddler much as 30 Respondentts, and the sample 30 Respondentts were taken by total sampling with the mother’s role variable. The research instrument using a questionnaire, then processed with the Editing, Scoring, Coding and Tabulating.The results were obtained from 30 Respondentts, Respondentts who passivity as much as 23 Respondentts (76.6%) and that being active 7 Respondentts (23.4%). Based on the research results, it can be concluded that the mother's role in providing a healthy eating patterns in children aged 3-5 years is almost entirely passive. Midwife are expected to motivate the mother so that the mother is able to apply the information that has been obtained about giving a healthy eating patterns for their children